High genetic polymorphism of relapsing P. vivax isolates in northwest Colombia (2011)
ABSTRACT: Genetic diversity of Plasmodium populations has been more extensively documented in Colombia for Plasmodium falciparum than for Plasmodium vivax. Recently, highly variable microsatellite markers have been described and used in population-level studies of genetic variation of P. vivax throughout the world. We applied this approach to understand the genetic structure of P. vivax populations and to identify recurrence-associated haplotypes. In this, three microsatellite markers of P. vivax were amplified and the combined size of the fragments was used to establish genotypes. Patients from an ongoing treatment efficacy trial who were kept either in endemic or non-endemic regions in the northwest of Colombia were included in the study. In total 58 paired clinical isolates, were amplified. A total of 54 haplotypes were observed among the two regions. Some haplotypes were exclusive to the endemic region where the highest degree of polymorphism was detected. In addition, we confirmed the different genotypes of recurrent-relapsing and primary infection isolates suggesting the activation of heterologous hypnozoite populations. We conclude that analysis of the three microsatellites is a valuable tool to establish the genetic characteristics of P. vivax populations in Colombia.